Romantyczny dyskurs o modelu rodziny w “Czasach Wincentego Pola” - Półchłopek, Tadeusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Having different programmes and placing themselves on the margin of the reduced political life, romantics moved the imperative of building the world around their ideals into the only possible sphere – culture. Writers called for the remedial teaching of women, condemned the worship of marriages entered solely for financial reasons, demanded the democratization of the model of a family, created the standard of a mother and a gifted citizen capable of love and dedication. Such a strategy was expected on time when developmental mechanisms of the individual and societies reveal anthropocentric axiological horizons which would become a new bedrock to the identity.